Conversations With History : Afghanistan and Pakistan (2003)
[Dt.:] Die vorliegende Seite enthält ein Gespräch über islamischen Fundametalismus zwischen Harry Kreisler, dem Executive Director des Institute of International Studies an der University of California und Pamela Constable von der Washington Post. Das Gespräch behandelt die Wahlen 2008 in Pakistan und deren Bedeutung für die USA sowie die Entwicklungen in Pakistan und Afghanistan seit dem 11. September. Die Videoaufzeichnung ist Teil einer umfangreichen und frei verfügbaren Sammlung akademischer Vorträge und Gespräche, die über die Webseite des University of California Television angeschaut werden können. - [Engl.:] On this edition of Conversations with History, Harry Kreisler, the Executive Director of the Institute of International Studies at the University of California at Berkeley talks with Pamela Constable of the Washington Post about changes in Afghanistan and Pakistan since 911 and the implications of the 2008 Pakistan elections for U.S. Pakistan relations. This conversation is part of the University of California Television programme which contains a huge collection of academic talks and presentations which are accessible via the website